2016
DOI: 10.1071/an14545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cut type and post-mortem ageing on the technological quality, textural profile and sensory characteristics of horse meat

Abstract: The present study was conducted to investigate the effects of cut type and ageing period on the technological quality, colour, texture and sensory characteristics of horse meat. Nine different cuts: loin, shoulder chuck roll, shank, outside round, tenderloin, shoulder clod, brisket, top round and striploin from 28-month-old female horses were used in the present investigation. The cuts were randomly assigned into 2, 10, 20 and 30 days’ ageing groups and ageing was carried out in a chilling room (2 ± 2°C). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 36 publications
13
13
1
Order By: Relevance
“…Whereas, the other remaining muscles (GM, BF, and SM) showed no pH changes up to 360 days of frozen storage. The ultimate pH values of non-frozen (day 0) or frozen muscles in this study were almost similar to values reported for the fresh horse muscles in literature [ 1 , 5 , 6 ]. This study for the first time, we assessed the effect of frozen storage duration on horsemeat pH values, and these obtained results suggest that there were differences in biochemical changes (e.g., glycolytic rate/or others) among the horse muscles before freezing or during freezing/thawing process.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Whereas, the other remaining muscles (GM, BF, and SM) showed no pH changes up to 360 days of frozen storage. The ultimate pH values of non-frozen (day 0) or frozen muscles in this study were almost similar to values reported for the fresh horse muscles in literature [ 1 , 5 , 6 ]. This study for the first time, we assessed the effect of frozen storage duration on horsemeat pH values, and these obtained results suggest that there were differences in biochemical changes (e.g., glycolytic rate/or others) among the horse muscles before freezing or during freezing/thawing process.…”
Section: Resultssupporting
confidence: 89%
“…Jeju female breed horses (n = 8) with their live weight of about 280 to 350 kg obtained from a local farm in Jeju province, Korea, were used in the present study. The raising procedures, feed content and feeding regimes applied for the animals were similar to those described in our previous study [ 5 ]. The animals were transported from the farm to the abattoir using an animal transporter truck and attempts were made to minimize stress in the animals.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations